New Characterizations and Representations of the Bott–Duffin Inverse - Jiabao Wu; Kezheng Zuo; Dragana S. Cvetković-Ilić; Honglin Zou (Journal of Mathematics)
The paper focuses on the class of the Bott–Duffin inverses. Several original features of the class are identified and new properties are characterized. Some of the results available in the literature are recaptured in a more general form. BD matrices are also introduced and some properties are given.